From research on determinants of emotional competence - Matczak, Anna; Martowska, Katarzyna (Studia Psychologica: Theoria et praxis, 2011)
The paper presents the research on the relations between emotional competence and selected intellectual abilities along with temperament traits postulated by Jan Strelaus Regulative Theory of Temperament. The subjects were adults at age from 19 to 39. Emotional competence was measured with the PKIE (Popular Questionnaire of Emotional Intelligence, by Matczak at al.), emotional ability with the test TRE (Emotion Understanding Test, by Matczak and Piekarska), social and verbal abilities by tests selected from the API-Z battery (by Matczak at al.), and temperament traits by the FCZ-KT questionnaire (Formal Characteristics of Behavior, by Zawadzki and Strelau). Weak connections emotional competence with social and emotional abilities were found. Relation between emotional competence and temperament traits appeared to be stronger, especially those for activity and briskness (positive), and emotional reactivity (negative). Additionally, the interesting differences in the results, depending on subjects’ gender and the type of competence (connected with experiential and strategic emotional intelligence) were also found.